Metabolic and ruck performance effects of a novel, light‐weight, energy‐dense ketogenic bar. Issue 5 (13th March 2023) - Buga, Alex; Crabtree, Chris D.; Stoner, Justen T.; Decker, Drew D.; Robinson, Bradley T.; Kackley, Madison L.; Sapper, Teryn N.; Buxton, Jeffrey D.; D'Agostino, Dominic P.; McClure, Tyler S.; Berardi, Anthony; Cline, Shawn; et al.
Abstract : New Findings: What is the central question of the study? Can a novel, energy‐dense and lightweight ketogenic bar (1000 kcal) consumed 3 h before exercise modulate steady‐state incline rucksack march ('ruck') performance compared to isocaloric carbohydrate bars in recreationally active, college‐aged men? What is the main finding and its importance? Acute ingestion of either nutritional bar sustained ∼1 h of exhaustive rucking with a 30% of body weight rucksack. This proof‐of‐concept study is the first to demonstrate that carbohydrate bars and lipid bars are equally feasible for preserving ruck performance. Novel ketogenic nutrition bars may have military‐relevant applications to lessen carry load without compromising exercise capacity. Abstract: Rucksack marches ('rucks') are strenuous, military‐relevant exercises that may benefit from pre‐event fuelling. The purpose of this investigation was to explore whether acute ingestion of carbohydrate‐ or lipid‐based nutritional bars before rucking can elicit unique advantages that augment exercise performance. Recreationally active and healthy males ( n  = 29) were randomized and counterbalanced to consume 1000 kcal derived from a novel, energy‐dense (percentage energy from carbohydrate/fat/protein: 5/83/12) ketogenic bar (KB), or isocaloric high‐carbohydrate bars (CB; 61/23/16) 3 h before a time‐to‐exhaustion (TTE) ruck. Conditions were separated by a 1‐week washout. The rucksack weight was standardized to 30% of bodyweight. Steady‐state treadmill pace was set at 3.2 km/h (0.89 m/s) and 14% grade. TTE was the primary outcome; respiratory exchange ratio (RER), capillary ketones ( R ‐β‐hydroxybutyrate), glucose and lactate, plus subjective thirst/hunger were the secondary outcomes. Mean TTE was similar between conditions (KB: 55 ± 25 vs. CB: 54 ± 22 min; P =  0.687). The RER and substrate oxidation rates revealed greater fat and carbohydrate oxidation after the KB and CB, respectively (all P  < 0.0001). Capillary R ‐βHB increased modestly after the KB ingestion ( P  < 0.0001). Neither bar influenced glycaemia. Lactate increased during the ruck independent of the condition ( P  < 0.0001). Thirst/fullness perceptions changed independent of the nutritional bar consumed. A novel KB nutritional bar produced equivalent TTE ruck results to the isocaloric CBs. The KB's energy density relative to CB (6.6 vs. 3.8 kcal/g) may provide a lightweight (–42% weight), pre‐event fuelling alternative that does not compromise ruck physical performance.